Ionic liquids catalyzed lignin liquefaction: mechanistic studies using TPO-MS, FT-IR, RAMAN and 1D, 2D-HSQC/NOSEY NMR - Singh, Sandip K.; Dhepe, Paresh Laxmikant (Green Chemistry, 2016)
Valorization of a profusely available alternate resource, biomass and in particular its 3-D intricate component lignin into low molecular weight aromatic products are used as platform chemicals and fuel additives, and developing a low temperature catalytic process is imperative in preserving atom efficiency. Ionic liquids, due to their unique properties, offer an advantage to develop such methods under milder conditions. Herein, we show use of -SO3H functionalized imidazolium based various recyclable Bronsted acidic ionic liquids (BAILs) in catalytic quantity under ambient pressure at 120 degrees C for depolymerization of lignin (60 000 g mol(-1)) into THF soluble products with high efficiency (78% yield, 95% +/- 5% mass balance). The decoding of this efficiency by 1D and 2D (HSQC/NOSEY) NMR, FT-IR and RAMAN studies exemplify that the -OH group(s) interact with the electron deficient BAIL cation. The mechanistic insights unraveled in this study open a plethora of opportunities to design catalysts for developing efficient processes.

Isolation of lignin by organosolv process from different varieties of rice husk: Understanding their physical and chemical properties - Singh, Sandip K.; Dhepe, Paresh Laxmikant (Bioresource Technology, 2016)

Effect of structural properties of organosolv lignins isolated from different rice husks on their liquefaction using acidic ionic liquids - Singh, Sandip K.; Dhepe, Paresh L. (Clean Technologies and Environmental Policy, 2018)
Lignin is the only naturally available sustainable resource of aromatic compound on the Earth. Depending on the properties of lignin and the reaction conditions employed for the liquefaction, it is observed that the product distribution alters. Since ionic liquids (ILs) are considered as green and have tuneable properties, in the current work, imidazolium-based acidic ILs were employed to liquefy organosolv lignins derived from different varieties of rice husks. When liquefaction was carried out at 120 A degrees C for 1 h 36% yield for EtOAc- and DEE-soluble products with high mass balance (97 +/- 3%) was observed. The detailed characterisations of lignins and organic solvent-soluble products were done by variety of techniques [GC-MS, FT-IR, UV-Vis, 2D (HSQC) NMR], and based on this, the correlation between activity and properties of catalyst and lignin was established. Depolymerisation of organosolv lignin (derived from three rice husks) into aromatic product was done, and experimental correlation studies were performed in both.

Experimental evidences for existence of varying moieties and functional groups in assorted crop waste derived organosolv lignins - Singh, Sandip K.; Dhepe, Paresh L. (Industrial Crops and Products, 2018)
Isolation of organosolv lignins (ORGLs, water:ethanol, 180 degrees C, 1 h, 93 +/- 5% mass balance) from various lignocellulosic materials like rice husk (RH), wheat straw (WS), bagasse (BG) & wood chips (WC) was done and experimental evidences are provided to perceive the differences in the structures of isolated lignins. To achieve this on bulk level, lignins were characterized by XRD, GPC, TGA & elemental analysis and on molecular level using UV-vis, ATR, 1D/2D HSQC NMR techniques. Besides isolated lignins, crop wastes and pulps were also characterized to divulge details on their properties. It was revealed that lignins have varying concentrations of sinapyl (S), coniferyl (G) and p-coumaryl alcohols (H) and tricin (T) moieties. While, Tricin (T) type lignin moieties are observed only in RH and WS derived lignins, RH derived lignin has higher concentration of side chains than other isolated lignins. Additionally, it is discovered that most lignins have G as main moiety.

Novel synthesis of immobilized bronsted- acidic ionic liquid: application in lignin depolymerization - Singh, Sandip K.; Dhepe, Paresh L. (Chemistryselect, 2018)
Designing of efficient catalyst for the valorization of lignin is a topic of long neglect due to intrinsic properties of lignin. We show designing of an efficient, stable and recyclable Immobilized-Bronsted acidic ionic liquid (I-BAIL), which was further used as a solid acid catalyst for the depolymerization of lignin. The synthesized I-BAIL catalyst with sulfonic acid (-SO3H) groups was found to be stable until 250 degrees C and has 42.2 wt.% loading of BAIL anchored on silica framework. The detailed characterization (elemental, Thermogravimetric analysis, Fourier transformation-infrared, Nuclear magnetic resonance) of catalyst disclosed formation of strong covalent bond between Si and carbon of BAIL, which in turn is responsible for achieving a stable catalyst. The catalyst could successfully depolymerize range of lignin substrates with high molecular weight (60000 Dalton) at 200(degrees)C in 1 h to achieve 90% yield of tetrahydrofuran soluble products with good mass balance. The formation of products and correlation of products with lignin was achieved with the help of Nuclear magnetic resonance, gel permeation chromatography, gas chromatography, gas chromatography-mass spectrometry, high performance liquid chromatography etc.

Formic-acid-induced using recyclable-ionic liquids as catalysts for lignin conversion into aromatic co-products - Singh, Sandip K.; Dhepe, Paresh L. (Waste and Biomass Valorization, 2019)
Lignin has been widely named as a sustainable and renewable bioresource of energy, fuels, chemicals and materials, particularly phenolic chemicals production on Earth. These bio-derived compounds are in great potential need of biorefinery to valorize complete plant biomass. Lignin depolymerization showed a great promise approach to convert into low molecular aromatic products. In this report, high molecular weight (54,000 Da) lignin depolymerization into maximum yields (87%), (>= 95 +/- 6% mass balance) using a formic acid along with dual (-SO3H) functionalized imidazole-based recyclable (4 times) Bronsted acidic ionic liquids (BAILs) as catalysts have been investigated in H2O-CH3OH (1:5, v/v) at 120 degrees C for 1 h. The structural correlations between the lignin and aromatic products were studied by bulk (CHNS, GPC, etc.) and molecular (UV-Vis, FT-IR, NMR (1D/2D) levels experimental techniques. Additionally, the identification of aromatic products was carried out by applying HPLC, GC and GC-MS techniques. Graphic Addition of a formic acid into Bronsted acidic ionic liquids improved the catalytic efficiency significantly for lignin depolymerization into 87% low molecular weight aromatic products. [GRAPHICS] .
Keywords: Bulk and molecular levels analysis; depolymerization; Dual functionalized ionic liquids; Formic acid; lignin

Lignin conversion using catalytic ionic liquids: understanding the role of cations, anions, and hammett acidity functions - Singh, Sandip K.; Dhepe, Paresh L. (Industrial & Engineering Chemistry Research, 2019)
Because it is undisputable that lignin depolymerization is a must to make the biorefinery concept economically feasible, several efforts are put toward it; however, a lot of catalyst designing is required to achieve efficient depolymerization activities. In this work, we show a systematic approach in the synthesis and characterization of ionic liquids (ILs) with varying combinations of cations (imidazole, benzimidazole, phosphonium, and ammonium) and anions (HSO4, PTS (p-toluenesulfonate), Cl, H2PO4, SnCl3, FeCl4, and CuCl3) for the depolymerization of lignin into low-molecular weight aromatic fractions (<220 g/mol) under mild reaction conditions (120 degrees C, 1 h, ambient pressure). In a methodical approach, effects of various reaction parameters such as temperature (70-170 degrees C), time (15-360 min), pressure (N-2, 0.5-3 MPa), solvents and substrate, and so forth were studied to achieve best activity. Among all the catalysts, IL with the imidazolium cation and HSO4 as the anion showed best activity (78% yield). Subsequent to depolymerization, three aromatic monomers (5 wt % pure vanillin) were isolated using flash column chromatography. These aromatic monomers were characterized using gas chromatography (GC), GC-mass spectrometry, and NMR techniques for their purity. Hammett acidity functions (H-0) of ILs were measured using UV-vis photo-spectroscopy, and values are correlated with lignin depolymerization results. Lignin and tetrahydrofuran-soluble products were thoroughly characterized using assorted physicochemical techniques such as NMR (H-1 and C-13), gel permittivity chromatography, thermogravimetric analysis, and so forth. The catalyst was recycled up to six runs and showed similar results in consecutive reactions.

Alpha-, beta- and gamma-cellulose quantification and two-stage concentrated-dilute acid lignin recovery from three rice husks: lignin characterization and depolymerization - Singh, Sandip K.; Dhepe, Paresh L. (Waste and Biomass Valorization, 2022)
Investigations on the compositional analysis of lignocellulosic materials and their properties upon recovery are essential to be studied in order to examine the effects of recovery method, their dependency on the substrate, etc. In this work, three rice husks (RHs) samples were subjected for alpha-, beta- and gamma-cellulose, pentosan, and silica quantifications. Correlations between the source of biomass, lignin recovery by two-stage concentrated and dilute sulphuric acid treatment, their properties and their depolymerization into low molecular mass aromatic fractions using homogeneous and heterogeneous Bronsted acidic ionic liquids as catalysts, is carried out. Correlation between the properties of RHs and recovered lignin were performed using destructive (CHNS, TGA, ICP-OES, etc.) and non-destructive (XRD, UV-Visible, FT-IR, and C-13 CP-MAS NMR) analytical techniques. It was observed that the recovered lignin was polysaccharides free and associated with dibenzodioxocin, spirodienone, and tricin type moieties with variable intensities. The effects of lignin structures showed a change of depolymerisation product pattern. [GRAPHICS] .
Keywords: Holocellulose; Homogeneous and heterogeneous catalysts; lignin; Rice husks

Lignocellulosic biomass analysis: acidic lignin recovery, characterisation, and depolymerisation - Singh, Sandip K.; Matsagar, Babasaheb M.; Dhepe, Paresh L. (Biomass Conversion and Biorefinery, 2024)
For the development of an effective lignocellulosic biomass conversion technology to biofuels and chemicals, the biomass composition analysis and their properties need to be characterised prior to biomass valorisation, including polysaccharide hydrolysis and lignin depolymerisation. In this work, a facile colorimetric titration method for the quantification of alpha-, beta-, and gamma-cellulose, pentosan, lignin, and silica percentages of wheat straw (WS) and two bagasse (BG I and II) samples was done. The result showed higher amounts of structural biopolymers (i.e. holocellulose and lignin (similar to 89.3%)) in BG compared to WS (81%) sample. Lignin recovery from BG (I and II) and WS samples was done by applying two-stage concentrated and dilute sulphuric acid hydrolysis, and maximum recovery (i.e. 21.5%; acid soluble +insoluble) of lignin obtained from BG II sample. Elemental and composition analysis results were represented substantial differences in lignin properties, including higher heat values (19.8 MJkg(-1)) of recovered lignin from BG II as well as high amounts of silica percentage from WS lignin. An intense Si-O-Si asymmetric stretching mode and/or C-O-C aliphatic aromatic ether (similar to 1100 cm(-1)) was characterised for lignin derived from WS. C-13 CP-MAS NMR exhibited variable intensities for dibenzodioxocin, spirodienone, and tricin moieties in recovered lignin samples. These lignin samples were processed for depolymerisation using homogeneous (1-methyl-3-(3-sulphopropyl)-imidazolium hydrogen sulphate) and heterogeneous (immobilised Bronsted acidic ionic liquid) catalysts to lower molar mass aromatic fractions and represented 89% and 92% organic solvent-soluble product yields respectively from WS-derived lignin.
Keywords: bagasse; Dibenzodioxocin; Holocellulose; Lignin depolymerisation; Spirodienone; Tricin; Wheat straw